Climate change through the essentials–nature's offering and humankind's sine qua non - Anderl, Thomas (Frontiers in Climate, 2023)
Climate change is decomposed into the driving terms allowing long-term projection of the natural and economic impacts. As a result, in the case of carbon emissions reduction by 2% per year from the present, the atmospheric CO2 concentration is expected to return to preindustrial values in about 1,000 years, temperature and sea level rise to approximately peak at 1°C and 5 m above the present levels by then, and the entailed economic burden to grow to 1.4% of the current global gross domestic product. Ninety percent of the required emissions reduction are anticipated achievable through cost neutrality. To take advantage of the potentially bearable impact, humankind is obliged to fulfill certain prerequisites near-time: (i) CO2 emissions reduction must be at least 2%/year at global level; (ii) economic growth may not continue to jeopardize emissions reduction efforts, thus far contributing with an emissions rise of 1.7%/year; (iii) due to the economic interlinkage, global coherence of regulatory measures must be established, proposedly commencing with a sizable group of countries, the rules comprising economic penalization of non-participants. The presented insight is associated with the potential to alter the social decision mode.